An approach for collaborative code reviews using multi-touch technology - Muller, S.; Wursch, M.; Fritz, T.; Gall, H. C. (2012 5th International Workshop on Co-operative and Human Aspects of Software Engineering (CHASE), 2012)
Code reviews are an effective mechanism to improve software quality, but often fall short in the development of software. To improve the desirability and ease of code reviews, we introduce an approach that explores how multi-touch interfaces can support code reviews and can make them more collaborative. Our approach provides users with features to collaboratively find and investigate code smells, annotate source code and generate review reports using gesture recognition and a Microsoft Surface Table. In a preliminary evaluation, subjects generally liked the prototypical implementation of our approach for performing code review tasks.